Gla rich protein (GRP) mediates vascular smooth muscle cell (VSMC) osteogenic differentiation, extracellular vesicle (EV) calcification propensity, and immunomodulatory properties - Maia, Teresa M. (2024)
Vascular calcification (VC) is a complex process involving vascular smooth muscle cell (VSMC) osteogenic differentiation, inflammation, and extracellular vesicle (EV) calcification and communication networks. Gla rich protein (GRP) is a calcification inhibitor involved in most of these processes. However, the molecular mechanism of GRP in VC and the specific characteristics, cargo, and functionality of calcifying EVs require further elucidation. Here, we use a combination of human ex vivo aortic fragments and primary vascular smooth muscle cell (VSMC) models to obtain new information on GRP function in VC and EVs released by VSMCs. We demonstrate that GRP inhibits VSMC osteogenic differentiation through downregulation of bone-related proteins and upregulation of mineralization inhibitors, with decreased mineral crystallinity in EVs deposited into the tissue extracellular matrix (ECM). EVs isolated by ultracentrifugation at 30K and 100K from the cell media (CM) and deposited in the ECM from control (CTR) and mineralizing (MM) VSMCs were biochemically, physically, and proteomically characterized. Four different EV populations were identified with shared markers commonly present in all EVs but with unique protein cargo and specific molecular profiles. Comparative proteomics identified several regulated proteins specifically loaded into MM EV populations associated with multiple processes involved in VC. Functional analysis demonstrated that 30K and 100K ECM-MM EVs with higher calcium and lower GRP levels induced macrophage inflammation. Our findings reinforce the functional relevance of GRP in multiple VC processes and suggest that ECM EVs released under calcification stress function as a new signaling axis on the calcification-inflammation cycle.